Corneal epithelial permeability to fluorescein in humans by a multi-drop method. - Sangly P Srinivas; Arushi Goyal; Deepti P Talele; Sanjay Mahadik; Rachapalle Reddi Sudhir; P Pavani Murthy; Sudhir Ranganath; Uday B Kompella; Prema Padmanabhan (PLoS ONE)
Purpose The permeability of the corneal epithelium to fluorescein Pdc is an indicator of the health of the ocular surface. It can be measured in a clinical setting by determining the accumulation of fluorescein in the stroma following administration of the dye on the ocular surface. Here we demonstrate a new multi-drop method for the measurement of Pdc by a spot fluorometer. Methods Twenty-nine healthy participants were recruited for this study. First, a probe-drop of fluorescein (0.35%, 2 μL) was instilled on the conjunctiva. The clearance of the dye from the tears was immediately measured using the fluorometer. Following this, two loading drops (2%; 6 μL each) were administered 10 min apart. Fifteen minutes later, the ocular surface was washed and fluorescence from the stroma Fs was measured. Permeability was calculated using Pdc = (Q x Fs)/ (2 x AUC), where Q is the stromal thickness and AUC is the area under the fluorescence vs. time curve for the loading drops. Results After the probe drop, the tear fluorescence followed an exponential decay (elimination rate constant; kd = 0.41 ± 0.28 per min; 49 eyes of 29 subjects), but the increase in Fs was negligible. However, after the loading drops, the measured Fs was ~ 20-fold higher than the autofluorescence and could be recorded at a high signal to noise ratio (SNR > 40). The intra-subject variability of kd was insignificant. Since fluorescein undergoes concentration quenching at > 0.5%, the value of AUC for the loading drops was estimated by scaling the AUC of the probe drop. The calculated Pdc was 0.54 ± 0.54 nm/sec (n = 49). A Monte Carlo simulation of the model for the multi-drop protocol confirmed the robustness of the estimated Pdc. Conclusions The new multi-drop method can be used in place of the single-drop approach. It can overcome a lack of sensitivity in fluorometers of high axial resolution. The Pdc estimated by the multi-drop method is ~ 11-fold higher than previously reported but closer to the value reported for other drugs with equivalent octanol/water partition coefficient.